Encapsulation of Extracted Oil from Mentha piperita in Alginate Beads - Shrestha, Kriti; Kunwar, Manish; Kunwar, Alina; Pokharel, Prayan (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Encapsulating essential oils derived from traditional medicinal flora within alginate beads represents an up-and-coming technique for enhancing their stability, bioavailability, and controlled release properties. In this study, we employed a Clevenger apparatus to extract the essential oil from Mentha piperita. The hydrodistillation process of M. piperita yielded an essential oil extraction of 0.27 Â± 0.05%. The ionic gelation methodology facilitates the cross-linking of alginate with Calcium chloride, forming a gel-like matrix that effectively encapsulates essential oil droplets within stable, gelled beads. The essential oil-loaded beads were quantified spectrophotometrically at a wavelength of 340 nm (Î»max). Furthermore, we evaluated and characterized the beads for size, weight analysis, sphericity, swelling behavior, dissolution kinetics, pH stability, drying rate, and accelerated stability studies. The size of alginate beads exhibited a significant increase concomitant with an elevation in sodium alginate concentration. The release profile of the oil content demonstrated a more sustained and regulated release within a phosphate buffer at pH 6.8 as opposed to that observed in 0.1N HCl.